Rheological characterization of κ-carrageenan/galactomannan and xanthan/galactomannan gels : comparison of galactomannans from non-traditional sources with conventional galactomannans - Pinheiro, A. C. (2011)
The synergistic interactions of two non-conventional galactomannans (Gleditsia triacanthos galactomannan (mannose/galactose ratio [M/G] = 2.82) and Sophora japonica galactomannan (M/G = 5.75)) with κ-carrageenan and xanthan were quantified and compared with those of two traditional galactomannans (guar gum—M/G= 1.8 and locust bean gum—M/G= 3.5) with the same polysaccharides. The main objective was to evaluate the effectiveness of the former as alternative galactomannan sources. The rheological behavior of the resulting binary systems was characterized using dynamic oscillatory measurements. For κ-carrageenan/galactomannans mixtures, the synergistic interactions were stronger for mixtures of 60/40 (% w/w) κ-carrageenan/locust bean gum, 60/40 (% w/w) κ-carrageenan/S. japonica galactomannan, 80/20 (% w/w) κ-carrageenan/guar gum and 60/40 (% w/w) κ-carrageenan/G. triacanthos galactomannan. For all xanthan/galactomannans systems, the maximum synergy was observed for a ratio of 20/80 (% w/w). The synergistic effects of κ-carrageenan/galactomannans and xanthan/galactomannans systems seem to depend not only on the M/G ratio but also on the fine structure of the galactomannans, since the strongest synergy was observed for locust bean gum followed by S. japonica galactomannan, guar gum and G. triacanthos galactomannan.